Which practice characteristics are associated with the quality of cardiovascular disease prevention in European primary care? - Ludt, Sabine; Campbell, Stephen; Petek, Davorina; Rochon, Justine; Szecsenyi, Joachim; van Lieshout, Jan; Wensing, Michel; Ose, Dominik (Implementation science, 2013)
Prevention of cardiovascular diseases (CVD) is a major health issue worldwide. Primary care plays an important role in cardiovascular risk management (CVRM). Guidelines and quality of care measures to assess CVRM in primary care practices are available. In this study, we assessed the relationship between structural and organisational practice characteristics and the quality of care provided in individuals at high risk for developing CVD in European primary care.
Gesehen am 08.06.2021